Direct Numerical Simulation of Oscillatory Flow Over a Wavy, Rough, and Permeable Bottom. Issue 3 (1st March 2018) - Mazzuoli, Marco; Blondeaux, Paolo; Simeonov, Julian; Calantoni, Joseph
Abstract: The results of a direct numerical simulation of oscillatory flow over a wavy bottom composed of different layers of spherical particles are described. The amplitude of wavy bottom is much smaller in scale than typical bed forms such as sand ripples. The spherical particles are packed in such a way to reproduce a bottom profile observed during an experiment conducted in a laboratory flow tunnel with well‐sorted coarse sand. The amplitude and period of the external forcing flow as well as the size of the particles are set equal to the experimental values and the computed velocity field is compared with the measured velocity profiles. The direct numerical simulation allows for the evaluation of quantities, which are difficult to measure in a laboratory experiment (e.g., vorticity, seepage flow velocity, and hydrodynamic force acting on sediment particles). In particular, attention is focused on the coherent vortex structures generated by the vorticity shed by both the spherical particles and the bottom waviness. Results show that the wavy bottom triggers transition to turbulence. Moreover, the forces acting on the spherical particles are computed to investigate the mechanisms through which they are possibly mobilized by the oscillatory flow. It was found that forces capable of mobilizing surface particles are strongly correlated with the particle position above the mean bed elevation and the passage of coherent vortices above them. Key Points: Hydrodynamic force acting on sediment particles is strongly affected by coherent vortex structures propagating close to the bed Transition to turbulence is induced by the wavy bed at a value of the Reynolds number significantly smaller than in absence of waviness The time development of the bed shear stress is shown and split into the viscous, turbulent, and "form" contributions